Prevalence of self-reported gynaecological problems in a community of district Srinagar Kashmir valley - Rasool, Mahbooba; Ayub, Taha; Samreen, Sheema (International Journal Of Community Medicine And Public Health, 2017)
Background: Gynaecological disorders are quite frequent in the community but still mortality is an indicator of maternal health. Treatment seeking behaviour depends upon the individual perceptions and attitudes towards health care. Methods: A community based cross sectional study in which 419 eligible women in the age group of 15-45 were enrolled and interviewed for the study. A semi structured pretested questionnaire was used. The questionnaire included information about the socio demographic characteristics of the students. Data was analysed using percentages. Results: The prevalence came out to be 20.28% which was percentage of women reporting one or more gynaecological disorders. 52.94% did not seek anywhere care or visited any health care facility. Conclusions: The study found a good percentage of women who self-reported one or more gynaecological disorder, which prompts one to find out various factors associated with this problem.